Paroxysmal pain as the only presentation of focal epilepsy. Issue 10 (20th July 2020) - Garcez, Daniela; Marques, Joana; Fernandes, Mariana; Foreid, John Peter
Abstract: Painful seizures can be the only feature of focal epilepsy. Its localization on a limb favors the epileptic etiology, while abdominal or cephalic paroxysmal pain is not so specific. Painful somatosensory seizures arise from operculo‐insular cortex. Abstract : Painful seizures can be the only feature of focal epilepsy. Its localization on a limb favors the epileptic etiology, while abdominal or cephalic paroxysmal pain is not so specific. Painful somatosensory seizures arise from operculo‐insular cortex.